A community faith centre based screening and educational intervention to reduce the risk of type 2 diabetes: A feasibility study. (October 2016) - Willis, A.; Roshan, M.; Patel, N.; Gray, L.J.; Yates, T.; Davies, M.; Khunti, K.
Highlights: We present data on screening yield and uptake to structured education delivered in faith centers. The data is relevant to the current debate on implementation of diabetes prevention programs. The data describes the performance of a risk score for diabetes and in a South Asian population. Abstract: Aims: People of South Asian origin experience higher rates of diabetes and complications of diabetes compared to white Europeans. Therefore, it is important to identify those with undiagnosed diabetes and those at high risk of developing diabetes, in order to intervene with lifestyle intervention to reduce risk and prevent complications. We conducted a study to assess the feasibility of delivering a faith centre based pathway for screening and referral to group education for high risk individuals to increase screening uptake and reduce diabetes risk. Methods: Opportunistic screening and early intervention strategy for people at risk of diabetes and cardiovascular disease in local faith centres. The screening consisted of a diabetes risk assessment tool and a near patient test for HbA1c. Participants found to be at high risk of diabetes (HbA1c 6–6.4%/42–46 mmol/mol) were offered a 'Walking Away from Diabetes' group educational intervention aimed at increasing exercise levels and reducing diabetes risk. Results: 252 participants were screened during four screening events. 202 participants (80.2%) gave consent for their data to be included in the analysis. 72.4% of participants were found to have a high diabetes risk score. 32 participants (15.8%) had a HbA1c result (6–6.4%/42–46 mmol/mol). Eight participants (4.0%) had a (HbA1c ⩾6.5%/⩾47 mmol/mol). Of those eligible for the diabetes prevention education programme, 18 participants (56.3%) attended. Conclusions: This study confirms that screening followed by group education within faith centre settings is feasible and acceptable to participants. The strategies chosen were effective in achieving a high screening yield and high uptake of group education.